On the role of interplanetary shocks in accelerating MeV electrons - Talebpour Sheshvan N; Dresing N; Vainio R; Afanasiev A; Morosan DE (EDP SCIENCES S A, 2025)
Context. One of the sources of solar energetic particle (SEP) events is shocks that are driven by fast coronal mass ejections (CMEs). They can accelerate SEPs up to relativistic energies and are attributed to the largest SEP events. New studies suggest that CME-driven shocks can potentially accelerate electrons to MeV energies in the vicinity of the Sun.
Aims. We focus on relativistic electrons associated with strong interplanetary shocks between 2007 and 2019 to determine whether the shocks can keep accelerating such electrons up to a distance of 1 AU.
Methods. We analyze observations by the High Energy Telescope (HET) aboard the STEREO spacecraft of potential electron energetic storm particle (ESP) events characterized by intensity time series that peak at the time of, or close to, the associated CME-driven shock crossing. We present a new filtering method to assess the statistical significance of particle intensity increases and apply it to MeV electron observations in the vicinity of IP shocks. We employ a STEREO in situ shock list, which contains a total of 587 shocks occurring at the two STEREO spacecraft. From this list, we identify 27 candidate events through visual inspection.
Results. Our method identifies nine clear cases where a significant increase of MeV electrons was found in association with a shock. Typically, the highest statistical significance was observed in the highest of the three HET energy channels (2.8-4.0 MeV). All nine cases are associated with shocks driven by IP CMEs that showed large transit speeds in excess of 900 km s-1. In several cases, multiple shocks were observed within one day of the shock related to the electron increase.
Conclusions. Although electron ESP events at MeV energies are found to be rare at 1 AU, our filtering method is not designed to identify a potential IP shock contribution from distances closer to the Sun. Observations from the Parker Solar Probe or Solar Orbiter taken during closer approaches to the Sun would likely provide clarity on the IP shock acceleration of electrons.